Diagnostic Accuracy of Ultrasound for Benign and Malignant Hepatic Masses Taking Computed Tomography as Gold Standard: Diagnostic Accuracy of Ultrasound for as Gold Standard - Aslam, Ariba; Nazir, Memona; Zain ul Abidin, Syed; Fatima, Zareen; Yousaf Farooq, Syed Muhammad; Zia, Saad; Ahmad, Waqar; Adrees, Nadia; Naeem, Savaira; Imtiaz, Areej; Fatima, Manahil; Rita, Ujala (Pakistan Journal of Health Sciences, 2022)
Detection of benign and malignant liver masses is very important for the treatment. Objectives: To determine the diagnostic accuracy of ultrasound for hepatic masses taking computed tomography as gold standard Methods: It was cross a sectional analytical study to.it involves 266 patients suffering from hepatocellular cell carcinoma age group 45 to 65 years visiting Department of Radiology THQ Hospital Hazro, both genders were included. Consecutive sampling method was used. The collection of data was done through questionnaire and analysis by using SPSS version 25. Results: This study enlisted the participation of 261 patients. The average age of all patients was 59.28 14 years, with a range of 45 to 65 years. It describes that the total number of true positive disease were 228 which was also detected on ultrasound. However, the occurrence of HCC is highest on CT scan when compared with adenoma and hemangioma. There were 28 patients with multiple lesions, with 71.4 % being malignant and 28.6 % being benign. On the other hand, 22 individuals had a single lesion, of which 36.4% were malignant and 63.6 % were benign (p 0.001). CT had a sensitivity of 96 % to diagnose a malignant lesion, a specificity of 88.4 %, an accuracy of 95.78 %, a positive predictive value of 98.70 %, and a negative predictive value of 73.33 %. Conclusions: The results of the present study therefore concluded that CT is a useful modality for the diagnosis of malignant liver masses.Ultrasound had high sensitivity, specificity for the hepatic masses. females were more effected than males. Among hepatic masses, HCC is the commonest.